A-199 The Barkley Deficits in Executive Functioning Scale (BDEFS): Personality index or a measure of executive functioning?. (17th August 2022) - Ikonomou, Vasilios C; Harrell, Murphy N; Aita, Stephen L; Myers, Melissa A; Hawley, Nanako A; Pizer, Jasmin H; Hill, Benjamin D
Abstract: Objective: The BDEFS was compared to objective executive functioning (EF) measures as well as five-factor model (FFM) personality traits. Methods: One hundred sixty-five participants (M=19 years old, SD=1.3; 72.7% female, 55.2% White, 35.2% African American, 4.8% Asian) completed IPIP-NEO Personality Inventory, BDEFS-Long Form, Neuropsychological Assessment Battery (NAB) EF module, and Trail-Making Test (TMT) Parts A and B. Results: EF measures were reduced to a single-factor score using EFA (TMT A and B; NAB Mazes, Categories, and Word Generation subtests) accounting for 34% of the variance. Regression predicting BDEFS total score from the EF factor score was not significant [F(1, 163)=.182; p =.67, r2=.001]. Stepwise multiple regression predicting BDEFS total score from FFM traits identified three significant predictors (neuroticism: β=.390, extraversion: β=.239, and conscientiousness: β=-.572) that accounted for 54% of the variance [F(5, 159)=36.78; p<.001, r2=.54]. Stepwise regression predicting the EF factor score from FFM traits was not significant [F(5, 159)=.57; p=.721, r2=.018]. Conclusions: Performance-based EF measures were not related to BDEFS total score supporting that different constructs are being measured. Personality traits accounted for a majority of variance in BDEFS performance but minimal variance for performance-based EF performance. These results suggest that personality traits are strongly related to an individual's appraisal of executive dysfunction.